A new Brachysira species from mountain lakes in northern Italy and Corsica. Issue 3 (3rd July 2021) - Cantonati, Marco; Angeli, Nicola; Arnaud, Elena; Galbiati, Matteo; Soróczki-Pintér, Éva; Lange-Bertalot, Horst
Abstract : A faintly heteropolar Brachysira species, with an acutely rounded headpole and a base pole which is sometimes slightly protracted, found in two lakes in northern Italy and Corsica, is described and named Brachysira chiaruccii sp. nov. This proposed new species can be differentiated from similar species by recognizable characters or character combinations: valve outline and symmetry, shape of the apices and of the central area, striation density, size, anchor-shaped terminal raphe endings (SEM feature), ecology. Brachysira chiaruccii sp. nov. is so far known to colonize oligotrophic, circumneutral, sufficiently buffered, moderately low conductivity mountain lakes, whilst the typical habitat of the most similar (North American) heteropolar Brachysira species ( B. ocalanensis ) is dystrophic, very low alkalinity and pH environments. The description is based on SEM and LM micrographs which document the full spectrum of shape variability along the size diminution series (including girdle views), plastid arrangement and morphology, and ecological preferences, in particular along the pH-alkalinity gradient.